The Effect of Work Commitment, Work Motivation, and Job Satisfaction on Employee Performance PT. Bangunindo Karya Utama - Dewi Iriani; Muhammad Rusydi; Ahmad AC.; Andi Mappatompo; Muh. Ikram Idrus (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to identify and analyze the influence of work commitment on employee performance, work motivation on employee performance, and job satisfaction on employee performance at PT. Bangunindo Karya Lutama. The research method used is quantitative, with data collected through a survey using questionnaires, involving a sample of 110 respondents. The data obtained were analyzed using Multiple Linear Regression Analysis to determine the relationships between the variables, utilizing the SPSS V.24 application. The results of the study indicate that: 1) Work commitment has a positive but not significant effect on employee performance, 2) Work motivation has a positive and significant effect on employee performance, and 3) Job satisfaction has a positive and significant effect on employee performance.